EFFECTS OF NANOPARTICLES IN SURFACTANT ON FOAM STABILITY FOR GAS MOBILITY CONTROL - CHEA, TAN BEE (2021)
Gas mobility is a common issue in petroleum reservoir due to significant viscosity difference between the injected gas and residual oil, as well as permeability contrast.